ISSUANCE PROCESS DILEMMA OF SURAT IZIN USAHA PENJUALAN LANGSUNG (SIUPL) (Regulation Implementation study on the Indonesian Minister of Trade Regulation Number: 32/M-DAG/PER/8/2008, 55/M-DAG/PER/10/2009 and the regulation of Head Indonesian Investment Coor - Fadila Nuuru Rohmah (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
Indonesia became the center of the trading due the strategic place which is located between the two continents, Asia and Australia, as well as between the two oceans, namely the Indian Ocean and Pacific Ocean. Firm which undertake any trading in Indonesia is obligated to have a permission from the Ministry of Trade. At the first, the issuance of Surat Izin Usaha Penjualan Langsung (SIUPL) is through the Ministry of Trade. However, with the issuance of President Decreee of Republik Indonesia Number 27 in 2009 about One Stop Services of invesment sector, SIUPL is delegated to Indonesia Invesment Coordinating Board (BKPM).Keywords: Dilemma, Direct Selling, Surat Izin Usaha Penjualan Langsung (SIUPL), Capital Investment